2011
DOI: 10.1111/j.1525-1470.2011.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cutaneous Plexiform Schwannomas as Initial Presentation of Neurofibromatosis 2 in a 9‐Year‐Old

Abstract: Neurofibromatosis 2 (NF2) is an autosomal-dominant disease caused by genetic mutations of the NF2 gene on chromosome 22. Patients are often diagnosed according to the presence of bilateral vestibular schwannomas and other tumors in the brain and spinal cord. In children, NF2 can present early with ocular findings and cutaneous tumors. We report here a 9-year-old girl who presented with multiple pigmented, slightly tender plaques on her scalp, face, and back that were revealed by histopathology to be plexiform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is a rare neoplasm of the neural sheath with a multinodular plexiform growth pattern. It may occur as an isolated lesion but there is a growing number of papers, including our study, reporting its coexistence with NF2 [38][39][40][41][42][43]. Ko et al [40] underline that although plexiform schwannoma is not a pathognomonic tumor for NF2 its presence in a patient may reflect underlying NF2.…”
Section: Pediatric Sporadic Vs Nf2-associated Meningiomasmentioning
confidence: 73%
“…It is a rare neoplasm of the neural sheath with a multinodular plexiform growth pattern. It may occur as an isolated lesion but there is a growing number of papers, including our study, reporting its coexistence with NF2 [38][39][40][41][42][43]. Ko et al [40] underline that although plexiform schwannoma is not a pathognomonic tumor for NF2 its presence in a patient may reflect underlying NF2.…”
Section: Pediatric Sporadic Vs Nf2-associated Meningiomasmentioning
confidence: 73%
“…Skin plaques have been described to correspond to plexiform schwannomas and are present in approximately 40% to 78% of children with NF2 . Although cutaneous signs are not conspicuous in NF2, these lesions have been suggested to be pathognomonic of NF2 . In the absence of any other evident NF2 clinical symptom, the medical record of the boy was reviewed, revealing a Bell-like palsy 2 years before that did not fully resolve, consistent with the NF2 disease.…”
Section: Resultsmentioning
confidence: 99%
“…1,4 Although cutaneous signs are not conspicuous in NF2, these lesions have been suggested to be pathognomonic of NF2. 4,7,[12][13][14] In the absence of any other evi-dent NF2 clinical symptom, the medical record of the boy was reviewed, revealing a Bell-like palsy 2 years before that did not fully resolve, consistent with the NF2 disease. After written informed consent was obtained, the complete skin plaque was removed for both further pathologic examination and genetic testing.…”
Section: Report Of a Casementioning
confidence: 99%
“…We believe that a greater understanding of the cutaneous manifestations of NF2 might facilitate early diagnosis and provide useful prognostic information, as on reviewing the literature we observed that skin lesions are a common presenting symptom in children with NF2 [11][12][13] and that all cases of cutaneous plexiform schwannomas described to date have occurred in young patients (4-28 years) or patients with a severe phenotype. [14][15][16][17][18][19][20][21] Moreover, in 2018, our group described a series of 7 patients with cutaneous plexiform schwannomas who all later developed a severe NF2 phenotype. 22 The aim of this study was to describe the clinical and histologic characteristics of cutaneous lesions in a cohort of patients with NF2 and to explore associations with phenotype and genotype based on the FGSS.…”
Section: Introductionmentioning
confidence: 99%